Land use change in soybean production systems in the Brazilian savanna: the role of policy and market conditions - Smith, J.; Cadavid, J.C.; Ayarza, Miguel Angel; Aguiar, J.L.P. de; Rosa, Roberto (1999)
This paper analyzes land use change in the Brazilian savanna and draws out policy implications about the adoption of resource management technologies. Resources management technologies are more likely to be adopted in areas experiencing a long-term deterioration in market conditions. Adoptions occurs primarily to increase long-term economic viability. Thus adoption may coexist with adverse environmental and social impacts. Past opportunities for asset accumulation appear to be a pre-condition for adoption, indicating the importance of building up the resilience of farmers (particularly the resource-poor) during good times. partnerships with the private sector can contribute significantly to technology diffusion.